Preparing for policy changes: social security expectations and pension scheme participation - Karen van der Wiel (Institute for the Study of Labor (IZA), 2008)
Western governments are currently contemplating how to adapt their Pay-As-You-Go pension systems so that these remain financially sustainable, even with an aged population. To the extent that policy-makers haven't already adapted their old age social security schemes, an ageing population thus leads to policy uncertainty in first pillar pensions. This paper sheds more light on the relationship between public and private savings by analyzing private pension scheme participation in the presence of such policy uncertainty. To do so, I assess the influence of subjective policy change expectations on voluntary pension scheme participation in the Netherlands. I find that participation in private pension schemes is higher for those who assign a high probability to the dismantlement of old age social security - in terms of lower benefits levels but more so in terms of a higher eligibility age. In addition, subjectively short-lived individuals who believe an eligibility age increase to be more likely than a benefit level cut, participate more. This could be explained by the fact that the relative cost of an eligibility age increase is larger for those who expect to live shorter. Individuals hence do prepare themselves for anticipated policy changes in old age social security and policy uncertainty in social security thus seems to lead to an increase in, or crowding in of, private savings.
Keywords: D84; 330; Ageing; savings behavior; social security; subjective probabilities; uncertainty; Alterssicherung; Gesetzliche Rentenversicherung; Rentenreform; Sparen; Entscheidung bei Unsicherheit; Private Rentenversicherung; Alternde Bevölkerung; Niederlande